The COVID-19 crisis and counter-cyclical policies in Brazil - Daniele Tavani (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
This paper considers both secular and medium-run trends to argue that the US economy was already vulnerable to shocks before the COVID-19 crisis. Long-run trends have shown a pattern of secular stagnation and increasing inequality since the 1980s, while the economy has displayed hysteresis during the sluggish recovery from the Great Recession. The immediate policy response through the Coronavirus, Relief and Economic Security (CARES) Act highlighted the coordinating role of fiscal policy on the economy, but also showcased limits, especially with regard to the paycheck protection program. The historical trajectory of the US economy before the COVID-19 crisis cast serious doubts on recent cries of 'overheating' and inflationary pressures that should supposedly arise from the 1.9 trillion relief package just signed into law by President Biden. Projecting forward to the long run, redistribution policies may provide useful first steps in reversing the trends of rising inequality and declining productivity growth that the US economy has seen over the last few decades.
Keywords: E21; E24; E25; O41; 330; path dependence; COVID-19; inequality; secular stagnation